(untitled) (Journal of Applied Oral Science, 2013)
Background: Photodynamic therapy (PDT) is a method of microbial reduction which can benefit periodontal treatment in areas of difficult access, such as deep pockets and furcations. The aim of this randomized controlled clinical trial was to evaluate the effects of PDT as an adjunct to full-mouth ultrasonic debridement in the treatment of severe chronic periodontitis. Material and Methods: Twenty-two patients with at least one pocket with a probing depth (PD) of ≥7 mm and one pocket with a PD of ≥5 mm and bleeding on probing (BOP) on each side of the mouth were included, characterizing a split mouth design. The control group underwent full-mouth ultrasonic debridement and the test group received the same treatment associated with PDT. The PDT was performed on only one side of the mouth and the initial step consisted of subgingival irrigation with 0.005% methylene blue dye. Two minutes after applying the photosensitizer, the low power laser – AsGaAl (Photon Lase III – PL7336, DMC, São Carlos -São Paulo, Brazil) was applied (660 nm, 100 mW, 9 J, 90 seconds per site, 320 J/cm 2 , diameter tip 600 µm). The following clinical parameters were evaluated: plaque index, gingival index, BOP, gingival recession (GR), PD, and clinical attachment level (CAL). All parameters were collected before, 1, 3 and 6 months after treatment. Results: An improvement in BOP, PD and CAL was observed after treatment, in both groups, but without any difference between them. After 6 months, the PD decreased from 5.11±0.56 mm to 2.83±0.47 mm in the test group (p